Comparative Study of Intravenous Dexamethasone and Methylprednisolone in Severe COVID -19 Patients Requiring Respiratory Support in Intensive Care Unit - Rajbanshi, Lalit Kumar; Rayamajhi, Anuj Jung; Bajracharya, Akriti; Shah, Rajat (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Numerous steroids have been used to combat the intense cytokine storms in severe COVID pneumonia. The study compares the use methylprednisolone and dexamethasone as an adjuvant steroid therapy in severe COVID-19 pneumonia. Methods: Prospective comparative study including total of 190 COVID-19 severe pneumonia cases admitted in intensive care unit with 93 patients randomly allocated to receive dexamethasone 6 mg and 97 patients allocated to receive methylprednisolone 1mg/kg in two divided doses both by intravenous route for 7 days. Mortality was compared as primary objective while oxygenation parameters and inflammatory markers, need for invasive mechanical ventilation, duration of ventilation, length of ICU-stay, incidence of multiorgan failure were assessed as secondary variables. Results: At day zero, the patient in methylprednisolone group had significantly lower PaO2/FIO2 ratio (258.3950.36 vs 285.1868.62, P=0.002). At day seven, methylprednisolone significantly improved PaO2/FIO2 ratio (266.5260.73 vs 244.8175.36, P=0.029) and there was substantial decrease in inflammatory markers CRP, Ferritin (P<0.05). PEEP requirement was significantly less with methylprednisolone (P=0.007). Methylprednisolone significantly reduced the incidence of multiorgan failure, need of invasive mechanical ventilation and duration of mechanical ventilation (P<0.05). However, there was no significant difference in terms of duration of ICU stay and 30 days in hospital mortality between the two groups Conclusions: Intravenous methylprednisolone significantly improved the oxygenation of COVID -19 pneumonia patients and decreased the inflammatory reactions as compared to similar dose of dexamethasone when given for week duration. However, methylprednisolone did not seem to be superior to dexamethasone in terms of improving mortality.